Design Optimization of Guided Flow Augmenters for Exhaust Air Energy Extraction - Singh, Enderaaj (Curtin University, 2024)
Harnessing urban wind energy using vertical-axis wind turbines is inefficient due to unpredictable wind conditions. This MPhil study explores extracting unnatural wind energy from cooling tower exhaust air using three-dimensional computational fluid dynamics. The turbine aspect ratio and solidity were investigated before optimizing the cycloidal diffuser design. Findings showed that using the optimized cycloidal diffuser, the HDWT power coefficient improved by 32.42% compared to the bare turbine in cooling tower wind conditions.